Pengaruh Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Terhadap Sikap Toleransi - Yessiana Ridloni Wulansari; Hasbi Siddik; Umar Sulaiman (Al-Fikr: Jurnal Pendidikan Islam, 2017)
This study discusses "The Effect of Learning Outcomes of Islamic Religious Education Subjectsto the Tolerance Attitudes of Class XI Computer Network Engineering Students at SMK Negeri 1Kota Sorong". The purpose of this research is to find out and describe the description of students'tolerance attitudes and the effect of learning outcomes of Islamic religious education subjects onthe tolerance attitude of XI grade students of Computer Network Engineering at SMK Negeri 1Sorong City. The approach used in this study is a quantitative approach and the type of thisresearch is ex post facto quantitative. The population in this study were all class XI ComputerNetwork Engineering totaling 79 students. The sample in this study was class XI ComputerEngineering Network 3 and 4, amounting to 30 students. The instrument used in this study was aquestionnaire using a Likert scale. The collected data is then processed using the help of the SPSSapplication program for windows type 20. Based on the results of the analysis with the help ofSPSS applications for windows type 20, the results show that the tolerance image of XI gradestudents of Computer Network Engineering is in the "good" category, which is located at intervalsof 57-59, with an average of 56.07; there is a significant influence between learning outcomes ofIslamic religious education subjects on student tolerance, this is indicated by a rxy value of 0.573;the coefficient of determination r2 (xy) of 0.328 and tcount of 3.698> ttable (0.3610). Based onthe r2xy determination coefficient of 0.328, it is understood that 32.8% of students' toleranceattitude is influenced by learning outcomes of Islamic religious education subjects, the remaining67.2% is influenced by other factors not disclosed in this study.